MAKNA KANJI DAN KIBUN DALAM NOVEL "KOKORO” KARYA NATSUME SOSEKI - Adorada Pramessyah Panukmolaksari (Japanology: The Journal of Japanese Studies, 2022)
The novel Kokoro by Natsume Soseki is a novel that is widely translated into many languages, especially in Indonesia language. The word kokoro have literal meaning of ‘heart', but when the word translated more it means ‘feeling'. In the novel itself, there are many uses of word ‘feeling' in Japanese language, especially the nouns kanji and kibun that are the focus on this research. Both nouns when translated into Indonesia language have the meaning ‘perasaan' (feeling). Knowing more of the detail about the similarity between the words, makes it easier to use it in sentences. Therefore, this research aims to analyze the similarity in meaning between the two nouns. The method used is descriptive qualitative method. This research uses the theory of lexical meaning, grammatical meaning, relation of meaning, and synonym itself to specify the differences between synonym of kanji and kibun. After analyzing the entire data, it can be concluded that the noun kanji have the meaning of ‘the atmosphere in everything'. The noun kibun means "a state of feeling which is not very strong and persists for a certain period of time” and "the atmosphere that is felt”.